Empowering the Potential of Local SMEs Based on the SDGs in Pagelaran Village - Dimas Wahyu Fahriski; Aurora Sabrina Imtinan; Agung Winarno; Agus Hermawan (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: This community empowerment program in Pagelaran Village aims to empower local SMEs, thereby boosting the local economy through the implementation of digitalization in SDGs entrepreneurship to address the challenges of digital economic competition. Method: This program is implemented in five phases: identification, analysis, implementation, monitoring, and evaluation. Practical Applications: This initiative enhances the image of local SMEs in Pagelaran Village through professional product design and packaging, while marketing capabilities are strengthened through engaging social media content. Conclusion: Community service aimed at empowering local SMEs in Pagelaran Village can strengthen their capacity and competitiveness, thereby having a positive impact on the local economy.